Gas Chromatography/Mass Spectroscopy Analysis of Phytochemicals Present in Orange Peel Powder and in Bread Prepared Using It - Krishnamoorthy, Chandan; Uma, Soumya Krishnan; Jadhav, Pooja Prafull; Ghazal, Kashifa; Chidambaram, Ramalingam (Asian Journal of Chemistry, 2018)
Orange peel is a rich source of phytochemicals and flavouring agent used in bread making. The phytochemicals present in the orange peel powder and bread prepared using orange peel powder was analyzed by gas chromatography/mass spectroscopy (GC/MS). The result shows that the methanolic and hexane extracts of orange peel powder contains phytocompounds with nature of fatty acids, ketones, cycloalkanes, sugar compounds, saturated hydrocarbons, amino acids, polyols, essential oil, carboxylic acids and antioxidants; out of which amino acids, aldohexose sugar and polyols shows higher peaks. But they were absent in the bread prepared with orange peel powder, which would have degraded due to high baking temperature. However, it shows the presence of boric acid, dehydrating agent, acylating reagent, alkane, saturated fatty acid and organic compounds. Out of which boric acid shows the highest peak. Considering, hexane extract both the orange peel powder and bread prepared using it shows the presence of fatty acids and hydrocarbon based phytocompounds.